In-line control of polarization sensitivity for fiber-optic biconical fused single-mode couplers - Basiladze, G.D.; Dolgov, A.I.; Berzhansky, V.N. (Functional Materials, 2004)
The possibility to use the fiber-optic coupler input port as the polarization vector rotator of linearly polarized light introduced therein to control the coupler polarization sensitivity has been demonstrated in experiment. The experimental dependences of the polarization vector rotation at the fiber coil output on the fiber straightening extent are presented. Экспериментально продемонстрирована возможность использования входного порта волоконно-оптического разветвителя в качестве вращателя вектора поляризации вводимого в него линейно поляризованного света для контроля поляризационной чувствительности разветвителя. Приведены экспериментальные зависимости угла поворота вектора поляризации света на выходе из витка волокна от степени выпрямления волокна. Експериментально продемонстровано можливість використання вхідного порту волоконно-оптичного розгалужувана як обертача вектора поляризації лінійно поляризованого світла, яке вводиться в порт, для контролю поляризаційної чутливості розгалужувана. Наведено експериментальні залежності кута повороту вектора поляризації світла на виході з витка волокна від ступеню випрямлення волокна.